Is data really the new “oil” of the 21st century or just another snake oil? Looking at uses and users (private/public) - Giuditta de Prato; Jean Paul Simon (International Telecommunications Society (ITS), 2015)
The best “guestimates” of the total amount of data in the world suggest that from 1987 to 2007 the total amount of analogue and digital data in the world grew from 3 billion gigabytes to 300 billion gigabytes. The so-called data explosion is driven by the combination of exponentially expanding amount of data available, the rapidly improving ability to process and analyse the data, and the deployment of the relevant infrastructures (broadband and ultra-high broadband networks, server farms, and devices such as smartphones, tablets and phablets). This research paper aims at marshalling facts about a notion that have been spreading quickly without being, most of the times, properly defined thereby remaining vague and all-encompassing. This article tries first to put the phenomenon into perspective, it then takes a closer look at some leading users of big data and introduces some of its uses for evidence-based policy-making.
Keywords: 330; Analytics 3.0; Big Data; Fat Data; Digital Dragons; ICT Internationalisation Internet of Things; Machine-to-Machine communication; Microlevel Analysis; Policy 3.0; R&D